Interactions of TTV with BKV, CMV, EBV, and HHV-6A and their impact on post-transplant graft function in kidney transplant recipients - Rosiewicz, Kamil S.; Blazquez-Navarro, Arturo; Kaliszczyk, Sviatlana; Bauer, Chris; Or-Guil, Michal; Viebahn, Richard; Zgoura, Panagiota; Reinke, Petra; Roch, Toralf; Hugo, Christian; Westhoff, Timm; Thieme, Constantin; et al. (Frontiers in Transplantation, 2024)
Background: Mono and combined reactivation of latent viruses occurs frequently under immunosuppressive therapy in kidney transplant patients. Recently, monitoring Torque Teno virus' (TTV) reactivation came more into focus as a potential biomarker for immune status. The surrogate characteristics of TTV reactivation on acute rejection, and the combined reactivation with other latent viruses such as CMV, BKV, EBV, and HHV-6A on allograft function is unknown so far.Methods: Blood samples from 93 kidney transplant recipients obtained during the first posttransplant year were analyzed for TTV/BKV/CMV/EBV/HHV-6A load. Clinical characteristics, including graft function (GFR), were collected in parallel.Results: With 100% and mean 5.72 copies/mL [log10], TTV had the highest prevalence and viral loads, respectively. We found 28.0%, 26.9%, 7.5%, 51.6% of simultaneous reactivation of TTV with BKV, CMV, EBV, and HHV-6 respectively. These combined reactivations were not associated with a significant reduced eGFR at month 12.Of interest, patients with lower TTV loads < 5.0 cp/ml [log10] demonstrated not only a higher incidence of acute rejection, but also unexpectedly a significantly earlier occurrence and higher incidence of BKV and HHV-6A reactivation. Correlations between TTV loads, other latent viruses and immunosuppressive medication were only significant from 6 months posttransplant.We could observe and support previously introduced TTV load thresholds predicting kidney allograft rejection. However, due to a possible delayed relation between immunosuppressive medication and TTV viral load adaptation the right time points to start using TTV as a biomarker might need to be further clarified by other and better designed studies.